Peran Pendidikan Agama Kristen di Gereja Terhadap Pemberdayaan Ekonomi Kreatif Jemaat di Era Digital - Boiliu, Fredik Melkias; Pasaribu, Martha Megawati (Lembaga Pengabdian kepada Masyarakat Universitas Langlangbuana, 2020)
This article examines how the role of Christian religious education in the church can empower the creative economy of congregations in the digital age. One of the church ministries that must be done is to be involved in increasing the welfare of the congregation through economic empowerment of the congregation. Economic empowerment is very important for the church to do, but in fact the church neglects it. In carrying out the ministry as God's worker in the world, the church does not only focus on spiritual matters, but more than that the church also becomes a servant in improving the quality of the social life of the congregation. The problems that occur in the church environment related to mental problems today are economic problems. The problems that occur in the church environment related to mental problems today are economic problems. Therefore, Christian religious education has a very important role to empower the creative economy in the church through teaching and mentoring in the congregation so that the congregation has the ability and skills and applies the creative economy in everyday life. The research method used in this research is literature and literature study. Literature review refers to an assessment of the concepts and theories used based on the available literature, especially from articles published in various scientific journals. Literature review serves to build concepts or theories on which to base studies in research.